Population-based epidemiological analysis of acute pyelonephritis and antibiotic prescription in Spain (2009–2018) - Jesús Redondo-Sánchez; Ricardo Rodríguez-Barrientos; Cristina Muntañola-Valero; Mª del Canto de-Hoyos-Alonso; Nuria Echave-Heras; Lucia Martínez-Manrique; Miguel Gil-García; Isabel del Cura-González (PLoS ONE, 2025)
Objectives To estimate the incidence of pyelonephritis in primary care in Spain from 2009 to 2018, assess the associated antibiotic prescriptions, and analyse trends by sex and age. Method This is a retrospective observational population-based national study using the Database for Pharmacoepidemiological Research in the Public Domain (BIFAP), which contains primary care electronic medical records , and is representative of the Spanish population. Patients with a diagnosis of pyelonephritis were included. Sociodemographic and clinical data were collected. Crude and adjusted incidence rates were calculated per 10,000 person-years by sex and age, and annual and global percentages of antibiotic use were calculated by sex, age, and antibiotic group. Trend analysis was performed using a joinpoint regression model. Results 24,888 cases of pyelonephritis were recorded with an incidence of 4.2/10,000 person-years (6.6 women vs 1.5 men). An annual decreasing trend was observed in women (AAPC average annual percentage change) –2.7 (95% CI −4.4;-0.9), men −3.0 (95% CI −4.5;-1.5), patients aged 18–64 years −2.9 (95% CI −4.7;-0.9) and ≥ 65 years −4.2 (95% CI −5.8;-2.4). The most frequently used groups of antibiotics were cephalosporins (38.7%), quinolones (30%), combined penicillins (22.2%) and fosfomycin (6.8%). Cephalosporin prescription predominated in women (39.8%), and quinolone prescription in men (40.3%). The most prescribed cephalosporins were third and second generation (21% and 17.7% respectively). A downward annual trend was observed in the global use of antibiotics AAPC −0.8 (95% CI −1.4; −0.2), with an increasing AAPC 1.7 (95% CI −0.6; 3.4) in ≥65 years. Among the groups of antibiotics, the prescription of quinolones AAPC −6.9 (95% CI −31.7;17.3) and penicillins AAPC −8.7 (95% CI −11.2;-6.8) decreased and cephalosporins increased AAPC 19.0 (95% CI 12.2;26). Conclusions Women had a fourfold higher incidence of acute pyelonephritis than men, with a decreasing trend over the study period. Cephalosporins were the most commonly prescribed antibiotics in women, while quinolones were more common in men. An increasing trend in cephalosporin use and a decreasing in quinolone use were observed.